2012
DOI: 10.1121/1.3684737
|View full text |Cite
|
Sign up to set email alerts
|

Probing of laser-induced crack modulation by laser-monitored surface waves and surface skimming bulk waves

Abstract: All-optical monitoring of the nonlinear motion of a surface-breaking crack is reported. Crack closing is induced by quasi-continuous laser heating, while Rayleigh surface acoustic pulses and bulk longitudinal surface skimming acoustic pulses are also generated and detected by lasers. By exploiting the strong dependence of the acoustic pulses reflection and transmission efficiency on the state-open or closed-of the contacts between the crack faces, the parametric modulation of ultrasonic pulses is achieved. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The possibility to close the crack completely locally by the stationary heating has been recently proved experimentally. 25,26,39,40 However, if m < 1 then the clapping could continue with the increasing excitation of the crack. In particular, when m < 1 and r x¼0 te ð0; PÞ ) r cr the modulation of the side-lobes does not depend anymore on the excitation level…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The possibility to close the crack completely locally by the stationary heating has been recently proved experimentally. 25,26,39,40 However, if m < 1 then the clapping could continue with the increasing excitation of the crack. In particular, when m < 1 and r x¼0 te ð0; PÞ ) r cr the modulation of the side-lobes does not depend anymore on the excitation level…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Here we focus on acoustic waves propagating along the surface of a sample and interacting with a surface breaking crack [5,6]. Unlike the frequency mixing process described above, involving initially two monochromatic waves, we deal here with wide band acoustic waves (the pulse duration is typically of several nanoseconds).…”
Section: Principle Of the All-optical Probing Of A Thermally Stressedmentioning
confidence: 99%
“…69 In this study, localized irreversible microscopic modification in crack surfaces is monitored by utilizing the responses of laser-generated and laser-detected acoustic waves to laser-induced crack modulation. Through upgrading and improving of the experimental approaches developed in previous works, 66,67 for the first time, monitoring of the macroscopic behavior of crack motion, as well as microscopic modifications of crack surfaces (reversible/irreversible modifications of asperities) by optically inducing and probing the acoustoelastic phenomena, has been enabled. A pulsed laser was used to generate surface skimming longitudinal waves and Rayleigh-type surface acoustic waves in a cracked black glass, and a continuous wave laser was used to detect them in the beam deflection configuration.…”
Section: Introductionmentioning
confidence: 99%
“…76 Furthermore, in this study, the reported non-monotonic evolution of peak-to-peak amplitude of the mode-converted signal at the end of cooling time intervals after heating at various heating powers can be potentially used to evaluate the width of the crack in SHM. 64,66,67 Furthermore, optical generation and detection of acoustic waves presented in this study can be easily scanned over the surface of the sample; thus, linear laser ultrasonic techniques, such as time-of-flight diffraction (TOFD) 77 and scanning laser source, 29 can be realized when required in combination with the laser-induced thermoelastic loading of the crack. These techniques have been proven to be beneficial for crack detection, and numerous applications have been reported in many fields of SHM.…”
Section: Introductionmentioning
confidence: 99%